Constant-Resistance, Rigid, and Flexible Coupling Support Technology for Soft Rock Entrances in Deep Coal Mines:A Case Study in China - Yong Zhang; Chengwei Zhao; Ming Jiang; Jiaxuan Zhang; Chen Chen; Xiaoyu Zheng; Xiaoming Sun; Huichen Xu (Advances in Materials Science and Engineering)
The stability control of a soft rock roadway is a crucial problem for sustainable utilization of limited coal resources in deep mining practices. To solve it, the soft rock types and failure mechanism of −890 entrance surrounding rock have been analyzed, taking Daqiang Coal Mine of China as an engineering example. The analysis shows that the damage to the surrounding rock was characterized by asymmetry, large deformation, severe damage, and extended durations. The surrounding rock can be divided into high-stress-jointed-strong expansion soft rock based on S-M scanning and mineral analysis. Numerical simulation is used to reproduce the failure process of the original supporting system and analyze the deformation of the surrounding rock, range of plastic zone, and distribution of the stress field. The failure mechanism is thus defined for a deep soft rock roadway. Combined with the above studies, the deformation mechanics of the surrounding rock is summarized as type IABIIABIIIABC. The stability transformation mechanism of the surrounding rock is proposed, based on which the control principle of deformation stability of a surrounding rock is formed. According to the control principle, “high strength support controls the surrounding rock deformation. The large deformation of the flexible support system releases the accumulated energy to the surrounding rock, and long-term deformation of the surrounding rock is controlled by high strength truss support.” Meanwhile, the constant-resistance, rigid, and flexible coupling (CRRFC) support system is proposed. The numerical analysis demonstrated that the CRRFC support system can effectively reinforce the shallow surrounding rock and improve the bearing capacity. Simultaneously, the development of the surrounding rock malignant plastic zone is effectively controlled. The application results show that the large deformation of the roadway can be effectively controlled by the CRRFC support system, which provides applications for similar engineering.